Audiological Evaluation in Hypertensive Patients - Madhavi Pant; Upendra Bhandari; Deepa Malla; Aashika Khadka; Late Prof. Subhash Chandra Mishra (Current Research in Pharmaceutical Sciences, 2022)
Every fifth person is affected by impaired hearing. Hearing loss, regardless of commitment, has an impact on people’s quality of life, and even when acquired later in life, it develops gradually and impairs spoken communication, affecting sociability, employment, and earning potential. Instead of receiving social sympathy, the person is ridiculed. Among vascular diseases, arterial hypertension is the most common, causing pathological structural changes in the heart and blood vessels. By affecting the vascular system, high blood pressure can produce inner ear bleeding and alter perfusion, resulting in progressive or sudden hearing loss. The present research project is undertaken to serve as a basis for greater awareness of prevention and restoration of hearing loss occurring in association with systemic infirmities like silently progressing arterial hypertension. The purpose of this study is to evaluate the hearing functions of patients of both sexes with hypertension and compare it with normal individuals. To assess the possibility of reversibility of hearing loss with control of hypertension. A prospective comparative study including all patients with hypertension in one group and normal subjects in another who fulfilled the inclusion criteria in Nepalgunj Medical College during the time period of 1st December 2014 to 30th January 2016 was carried out. All the individuals were subjected to a thorough E.N.T. examination. The audiological evaluation was done with Special tests of audiometry. Blood pressure level was estimated at the primary visit and 3 subsequent visits. mild to severe degree of hearing loss was found in 16 subjects (32%) as compared to control cases (statistically significant). There was sensorineural hearing loss in 28 ears (13 Rt. Ears and 15 Lt. Ears) amongst hypertensives (statistically significant). Overall, moderately severe and severe hearing losses were more often associated with stage 1 hypertension than stage 2 as is observed for both ears which are statistically significant. The mean threshold of the hearing was 28.84±16.84 and 24.16±11.31 amongst stage 1 and stage 2 hypertensives respectively. There was no statistically significant alteration of the hearing status of the hypertensives on subsequent follow-up, baring 3 cases that showed some recovery on the last follow-up. Hypertension as compared to control cases has a statistically significant influence on the hearing status of subjects above 31 years of age. Present data show that they have only marginally raised threshold for speech frequencies and it is at 4 kHz and 8 kHz that they are most often affected with hypertension.